The Possibilities of Bronchoscopy and Endosonography in the Differential Diagnosis of Mediastinal Tuberculous and Metastatic Lesions - I. V. Sivokozov; G. V. Evgushchenko; Yu. S. Berezovskiy; D. V. Sazonov; N. L. Karpina (Вестник рентгенологии и радиологии)
This clinical case shows the experience in concurrently using video-assisted bronchoscopy and endosonography in a patient with mediastinal adenopathy for differential diagnosis between tuberculous and metastatic changes. It demonstrates the possibilities and limitations of using both classical bronchoscopy and transesophageal endosonography with a EUS-b-FNA using echobronchoscope.